Exploring the Flare Phenomenon in Patients with Castration-Resistant Prostate Cancer: Enzalutamide-Induced PSMA Upregulation Observed on PSMA PET - van der Gaag, Suzanne; Vis, André N; Bartelink, Imke H; Koppes, Josephina C C; Hodolic, Marina; Hendrikse, Harry; Oprea-Lager, Daniela E (Journal of nuclear medicine, 2025)
Androgen receptor-targeting agents, particularly enzalutamide, show promise in enhancing prostate cancer diagnostic and therapeutic strategies by modulating prostate-specific membrane antigen (PSMA). Methods: A retrospective clinical cohort study investigated 9 men with metastatic castration-resistant prostate cancer on enzalutamide. PSMA PET/CT scans were obtained before and after enzalutamide initiation to assess PSMA expression changes. Lesions and organs at risk were evaluated visually and semiquantitatively. The flare phenomenon was characterized by a significant increase (≥20%) in the SUVmax of existing lesions or the appearance of new PSMA-positive lesions. Results: Exposure to enzalutamide led to a significant PSMA expression increase in 56% of assessed lesions (n = 42), with new lesions detected in 1 patient (11%). PSMA expression in organs at risk remained largely unaffected, indicating a tumor-specific response. Conclusion: Enzalutamide induces PSMA upregulation in metastatic castration-resistant prostate cancer, potentially enhancing diagnostic and therapeutic strategies. Further exploration of the flare phenomenon's clinical implications is warranted.
Keywords: nádory prostaty rezistentní na kastraci; Male; Glutamate Carboxypeptidase II; Positron Emission Tomography Computed Tomography; nitrily; lidé středního věku; Prostatic Neoplasms, Castration-Resistant; retrospektivní studie; senioři nad 80 let; Aged, 80 and over; benzamidy; flare phenomenon; enzalutamide; Humans; fenylthiohydantoin; Middle Aged; senioři; Antigens, Surface; mužské pohlaví; androgen receptor–targeting agent; ARTA; glutamátkarboxypeptidasa II; prostate cancer; Aged; Phenylthiohydantoin; Retrospective Studies; Benzamides; upregulace; Nitriles; prostate-specific membrane antigen; Up-Regulation; lidé; antigeny povrchové; PET/CT